Enhancing pragmatic competence in Kurdish EFL learners: The impact of a learner-centered approach - Zhikal Qader Salih; Mustafa Kurt (PLoS ONE, 2025)
The study investigates how a learner-centered learning approach (LCL) can help raise pragmatic competence in Kurdish learners of English as a foreign language (EFL). Pragmatic competence in using languages appropriately in societal contexts is not well-developed in Kurdish learners because of traditional grammar-based teaching practices. The study attempted to investigate how LCL could foster effective usage of English in natural communication contexts. Survey employed a quantitative research design using an adapted Discourse Completion Test (DCT) and formal questionnaires administered to 98 EFL learners and 12 teachers. Learners were taught LCL-based methodology for a defined period and included group activities, peer consultation, and context-based language activities. Statistical analysis established a significant improvement in students’ pragmatic competence subsequent to the intervention (Mean = 34.63, SD = 8.41) compared to pre-intervention ratings (Mean = 24.27, SD = 7.11), with a large effect size (Cohen’s d = 1.99). Further statistical analysis investigated correlations between students’ communicative strategies and attitudes and demographics (grade and gender). Teachers’ ratings provided additional insights regarding perceived effectiveness and difficulties in using LCL. Implications include the advantage to incorporating learner-centered pedagogies to enable pragmatic competency gain in EFL settings and the value in offering recurrent teacher professional development. These findings suggest that classroom application of LCL approaches can meaningfully contribute to English pragmatic gain among Kurdish speakers.